Impact of Soil Health Card in Unnao District of Uttar Pradesh - Sahay, Ratna; Singh, A K; Singh, Archana; Maurya, R C; Tewari, D K; Singh, Sunil (Indian Journal of Extension Education, 2020)
The impact of soil health cards (SHC) was assessed on 300 farmers in seven different villages of Unnao during the year 2017-19 on judicious use of fertilizers, bio fertilizers, organic fertilizers, soil health, cropping choice, cost reduction, farm profitability and sustainability. As per the adaptation of the SHC scheme, only 70 per cent of the farmers were able to understand the content of the SHC, of which 65 per cent farmers agreed that the recommendations were suitable for their agricultural practices and 60 per cent farmers followed theÂ recommendations of SHC. The major reduction has been recorded in the use of urea by 23 % followed by DAP fertilizer by 15 per cent. The major increase was recorded in Zinc fertilizer by 21 per cent especially in paddy. Use of other micronutrients improved up to 25 per cent. Most of the farmers were not using the bio fertilizers because of lack of knowledge and awareness. After SHC scheme a remarkable increase of 50 per cent was recorded in the use of bio fertilizers as seed, root and soil treatment. Overall, the performance of SHC scheme was satisfactory and need focus on quality of soil sample collection, timely distribution and SHCs, knowledge enhancement to farmers through various awareness campaigns and training programmes. To make this scheme successful it was observed that ensuring availability of recommended fertilizers and bio-fertilizers at village level at reasonable prices is key determinant.